[PP.27.23] GUIDELINES FOR PRIMARY ALDOSTERONISM: UPTAKE BY PRIMARY CARE PHYSICIANS IN EUROPE. (September 2017) - Monticone, S.; Mulatero, P.; Burrello, J.; Veglio, F.; Williams, T. A.; Funder, J. W.
Abstract : Objective: In 2008 the Endocrine Society published guidelines for the diagnosis and treatment of primary aldosteronism (PA), recommending screening testing in around 30% of the hypertensives. The present study was undertaken to establish the extent to which general practitioners (GPs) are aware of the guidelines and their familiarity with the management of PA. Design and method: The study took place in Italy and Germany. A questionnaire was administered to 250 physicians in Italy and 250 in Germany by the market research firm Stethos srl. The physicians chosen cared for at least 1000 monitored patients. Results: The median of patients seen by each physician resulted to be 1, 500 in both countries, 18% of which were hypertensives in Italy and 25% in Germany. Among hypertensive patients, 11% were considered to be affected by secondary hypertension (in 34.4% of cases attributed to an endocrine disease) and 7.6% displayed resistant hypertension in Italy; prevalence of secondary and resistant hypertension resulted 20% and 7.9% in Germany, respectively. At diagnosis of hypertension 50.4% of Italian GPs and 42.9% of German GPs request diagnostic tests to the patient; potassium levels are only requested by 43% GPs in Italy and 58% in Germany; renin and aldosterone measurement are required by around 8% of the GPs in both countries. Only 3% of the patients had the renin and aldosterone levels measured before the beginning of pharmacological therapy in both countries. In Italy, each GP follows an average of 3 PA patients, which results in a prevalence of PA of 1% among hypertensive patients; in Germany, each GP follows an average of 7 PA patients which results in a prevalence of PA of 2%. Conclusions: In conclusion, there is a significant gap between theory, as laid down in guidelines, and practice. It is likely that a similar gap exists throughout the world.